Geriatric pharmacotherapy: perceptions among UiTM final year pharmacy students / Mohamad Firdaus Abdul Lazim - Abdul Lazim, Mohamad Firdaus (2013)
With the aging of the Malaysia population, it is increasingly important for health professionals to understand how drug therapy principles for older adults may be different from those applied in younger adults. Just as medications can be metabolized and behave differently in children than in adults, so can medications act differently in older adults. This is especially the case in the frail elderly, those adults above the age of 65. Despite the importance of geriatrics, most health professional training programs, including those in pharmacy, lack adequate emphasis on geriatrics and the use of medications in older adults. The purpose of this research is to investigate Malaysian future pharmacists' perception in geriatric pharmacy aspects and to study the status of current pharmacy education content in current pharmacy curricula.